Photon-number-resolving detection enables single-photon LiDAR approaching the standard quantum limit - Feihu Xu (Light: Science & Applications)
Abstract A photon-number-resolving LiDAR approach and an active photon-number-filtering algorithm are proposed and demonstrated. This opens a new avenue for the development of single-photon LiDAR and relevant techniques to scientific study and real-world applications.